Tutela da efetividade dos direitos e deveres fundamentais pelos Tribunais de Contas: direito/dever fundamental à boa administração pública (e derivações) e direitos fundamentais à saúde e à educação - Cunda, Daniela Zago Gonçalves da (2011)
This study aims to demonstrate the importance of protection on fundamental rights and duties in the control to be exercised by Public Accounts, with emphasis on the fundamental rights to health and education, highlighting the fundamental principle of human dignity, the principle of sustainability (multidimensional features) and principles of public administration. It addresses the fundamental right/duty to good and public administration (as a possibility to reinforcement the legality of other fundamental rights) and some derivations: fundamental right/duty to good and public cyber@dministration (correlated to the principles of publicity and transparency and the necessary harmony of external control with social control). And this study demonstrates the different legal regime provided by the Brazilian constituent about fundamental rights to health and education and their special tutelage the possibility of allocating specific funds and providing by federal and state intervention when there is no application of the minimum constitutionally established (Article 212 from CRFB and Article 77 from ADCT) added of considerations about the necessary reserve on possible reserves. It presents a diagnostic application of secured funds in health and education by the state and cities in the south of Brazil and the necessary considerations for optimization of these investments. We propose new paradigms for the implementation of external control in the realization of fundamental rights/duties.